Ответы и объяснения

Лучший Ответ!
2013-06-26T13:49:06+00:00

Для синуса:

sin(\pi/2+a)=cosa

sin(\pi+a)=-sina

sin(3\pi/2+a)=-cosa

sin(2\pi+a)=sina

sin(\pi/2-a)=cosa

sin(\pi-a)=sina

sin(3\pi/2-a)=-cosa

sin(2\pi-a)=-sina

Для косинуса:

cos(\pi/2+a)=-sina

cos(\pi+a)=-cosa

cos(3\pi/2+a)=sina

cos(2\pi+a)=cosa

cos(\pi/2-a)=sina

cos(\pi-a)=-cosa

cos(3\pi/2-a)=-sina

cos(2\pi-a)=cosa

Для тангенса:

tg(\pi/2+a)=-ctga

tg(\pi+a)=tga

tg(3\pi/2+a)=-ctga

tg(2\pi+a)=tga

tg(\pi/2-a)=ctga

tg(\pi-a)=-tga

tg(3\pi/2-a)=ctga

tg(2\pi-a)=-tga

Для котангенса:

ctg(\pi/2+a)=-tga

ctg(\pi+a)=ctga

ctg(3\pi/2+a)=-tga

ctg(2\pi+a)=ctga

ctg(\pi/2-a)=tga

ctg(\pi-a)=-ctga

ctg(3\pi/2-a)=tga

ctg(2\pi-a)=-ctga